Relationship between university students’ depression levels and social media addiction in the covid-19 outbreak: a structural equation model - Dikmen, Melih (Journal of Dependence, 2021)
Objective: The purpose of this study is to examine the relationship between the depression levels of university students and their social media addiction in the COVID-19 pandemic through structural equation modeling. Method: The research was conducted according to the relational survey model, one of the quantitative research methods. The research was carried out on 211 university students at Firat University. Burns Depression Scale, was used to determine the depression levels of students. Social Network Addiction Scale was used to determine the social media addiction levels of the students. Results: There are significant relationships between depression level and social media addiction. A good fit was found between the obtained data and the predicted model. In this context, it has been determined that the depression levels of university students in the COVID-19 pandemic are the predictors of social media addiction. It has been observed that as the depression levels of university students increase, their social media addiction increases. Conclusion: Depression and social media addiction form a spiral structure that negatively affects each other. In this context, the concept of depression in social media addiction can be seen as a cause or a consequence.